Performance Motivation of Taekwondo Athletes: Coach-Athlete Relationship - Nugroho Arief Setiawan; Rizky Kinanti; Fitri Agung Nanda (CV. FOUNDAE, 2023)
Without motivation, an athlete will not feel motivated to perform optimally and will be desperate if he fails. The research was conducted to present a motivational relationship between coaches and athletes that describes how coaches can influence athlete motivation. The study was conducted on 62 taekwondo athletes. The instruments to collect data were a motivation scale with 27 items (? = 0.912) and the (CART-Q) Coach-Athlete Relationship Questionnaire with 22 items (? = 0,948). The data analyzed was assisted by the SPSS for Windows version 25. The results obtained from the calculation of the product-moment correlation were the r-value was 0.471, and the r2 value was 0.222, with p lower than 0.001. Thus, there was a relationship between coach-athlete relationship and performance motivation. The psychological processes in which constructive behavior positively influences intrinsic and extrinsic motivations were self-determined by athletes.